Reaksi Pasar terhadap Penerbitan Bond dan Sukuk - Ash Shidiqi, Fahmi Nashirul Haq (Jurnal Ekonomi & Keuangan Islam, 2018)
As a financial instrument in the company, bond and sukuk are still in great demand for investors. Each company’s decision will affect how investors react to the company’s performance. The six companies sampled in this research are PT Adira Dinamika Multi, PT Indosat, PT Adhi Karya, PT Sumarrecon Agung, PT Mayora, and PT TPS Food. The analytical method used is to compare the differences with conducting independent t-test for two observations of bond and sukuk issuance.The average of sample t-tets result on bond and sukuk found that no significant mean difference, it shows the position of the bond and sukuk equally give influence to share price of a company. In the statistic t test results of the six companies, the sukuk and bonds respond quickly to the information, but unlike the results grouped between the companies with the highest and lowest rating. At the best ratings bonds and sukuk responded well, even the level of significance is very high, the speed of information received is better than the bonds and sukuk the lowest.